Low incidence of venous thromboembolism in inflammatory bowel diseases: prevalence and predictors from a population-based inception cohort. (March 2014) - Vegh, Zsuzsanna; Golovics, Petra Anna; Lovasz, Barbara Dorottya; Kurti, Zsuzsanna; Gecse, Krisztina Barbara; Szita, Istvan; Balogh, Mihaly; Pandur, Tunde; Lakatos, Laszlo; Lakatos, Peter Laszlo
Abstract Objective. Patients with inflammatory bowel diseases (IBD) are considered to have an increased risk for venous thromboembolism (VTE). The aim of the present study was to analyze the incidence and risk factors of VTE in a population-based inception cohort in the Veszprem province database between 1977 and 2012. Material and methods. A total of 1708 incepted IBD patients were included (male/female: 879/829; CD (Crohn's disease): 648, age at onset: 29, interquartile range (IQR): 22–39; UC (ulcerative colitis): 1060, age at onset: 36, IQR: 26–50 years). Both in- and outpatient records were collected and comprehensively reviewed and followed up for a total of 21, 369 patient-years. Results. Twenty-two VTE events were identified in 19 patients (6 events in 5 CD and 16 in 14 UC patients). The incidence rate of VTE in IBD was 1.03 per 1000 patient-years. The risk of VTE in UC was associated with extensive location (odds ratio (OR): 3.25, 95% confidence interval (CI): 1.13–9.35), presence of fulminant episode during the disease course (OR: 4.15, 95% CI: 1.28–13.5), smoking (OR: 3.46, 95% CI: 1.14–10.5), and need for steroids (OR: 2.97, 95% CI: 0.99–8.92). Conclusion. The incidence of VTE was lower than previously reported. The incidence was higher in males and in UC it was associated with extensive disease, fulminant episodes, corticosteroids-requiring disease and smoking, but not with age at onset.